Pengaruh Profitability, Leverage, Dan Corporate Governance Terhadap Tax Avoidance - Thomas Felix, Jamaludin Iskak (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study was to examine the analysis of the effect of profitability, leverage, and corporate governance on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. Samples were selected using a purposive sampling method collected by 87 companies. Data processing techniques using the application program E-views version 10 and Microsoft Excel 2016. The results of this study indicate that profitability has no effect on tax avoidance, while leverage has a positive effect on tax avoidance and corporate governance has a positive effect on tax avoidance.